Library-faculty collaboration in the light of a business administration bachelor’s program: ‘The Scientific Wave’ - Näverå, Elisabeth; Olsson, Anna Karin (Nordic Journal of Information Literacy in Higher Education, 2022)
In contemporary digital society, information literacy is increasingly important and viewed as a necessary life skill for all ages, social groups, and professional sectors, hence also affecting higher education. Universities need to develop strategies and approaches to integrate these skills into course syllabi, assignments and assessments based on close library-faculty collaboration. However, librarians and faculty members in higher education traditionally often have separate agendas and limited collaboration. This paper illustrates the background and process of constructing a successful librarian-faculty partnership, as a shared framework entitled the ‘Scientific Wave’ throughout a bachelor’s program in business administration to enhance students’ critical thinking, research skills and information literacy in particular. A case study approach was applied, and data collection was conducted during 2014–2019. The outcomes of a shared framework and library-faculty collaboration are discussed from the perspectives of students, library, and faculty. Findings show that a shared framework based on close collaboration between librarians and faculty, strategic anchoring and visualization in curricula, syllabi, course objectives and assessments developed in line with the mission of the university have an impact on students’ information literacy skills during their education and after graduation. The Scientific Wave is a co-designed continuous framework based on the separate but complementary skills of librarians and faculty to provide students with tools for critical and creative thinking, research skills and lifelong learning in today’s digital society.